Efficacy and safety of systemic isotretinoin treatment for moderate to severe acne (insights from the real‐life clinical setting). Issue 6 (2nd November 2020) - Tolino, Ersilia; Skroza, Nevena; Proietti, Ilaria; Mambrin, Alessandra; Balduzzi, Veronica; Marchesiello, Anna; Maddalena, Patrizia; Michelini, Simone; Volpe, Salvatore; Bernardini, Nicoletta; Potenza, Concetta
Abstract: Acne is a chronic inflammatory relapsing disease that affect predominantly adolescents, with scarring as a frequent sequele. Early and appropriate therapy allows better management of the disease, longer remission, scars risk reduction, and improvement of quality of life. According to therapeutic algorithm, systemic isotretinoin can be used in severe acne and also in moderate forms resistant to other systemic treatments. The aims of this real‐life observational study were to determine and compare the effectiveness of isotretinoin evaluated by Global Acne Grading System and Acne Quality of Life in moderate and in severe acne, correlation between efficacy and cumulative dose of isotretinoin, tolerability, and recurrence rate. Moreover, the differences in efficacy and tolerability between male and female patients were compared. The treatment with systemic isotretinoin led to an improvement in acne severity and quality of life in all observed subjects.